ANALISIS KELENGKAPAN LEMBAR LAPORAN OPERASI PADA REKAM MEDIS PASIEN BEDAH DI RSU PKU MUHAMMADIYAH BANTUL - Dwi Ratna Sari; Nurvita Wikansari; Tri Ariani (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2022)
Background: Surgery is one of the services carried out by the hospital. The surgical report sheet must be completely filled out and signed by the doctor who performed the operation and must be made immediately after surgery, then entered into the patient's medical record. The incompleteness of filling out the surgical report can result in unclear sequence of procedures, this can cause serious problems, especially if it goes to court. The purpose of this study was to determine the completeness of the surgery report and the factor of incompleteness of the surgery report sheet at RSU PKU Muhammadiyah Bantul. Subjects and Method: This type of research is mixed methodology, data collection using observation checklist tables, and interview sheets. The population in this study was a surgical patient visit report sheet in April 2022 with a sample of 100 operating report sheets. The research subjects were 2 surgeons and 2 nurses. Results: The completeness of the surgical report for the identification section was 88.75%, the important report section was 95.58%, the authentication section was 100%, and the documentation section was good at 98%. The factor causing the incomplete surgical report is because of the doctors and nurses are busy, causing the operation report sheet to be incomplete. Conclusion: It is recommended that there be course to doctors and nurses regarding the importance of completeness of medical records, especially operating report sheets, and collaboration between medical record officers, nurses, and doctors who treat patients. Keywords: Completeness, Medical Records, Surgery Report, Surgical Patient.